Kepuasan Perawat Dalam Penggunaan Website Skrining Disfagia - Agianto; Setiawan, Abdul Bari; Setiawan, Herry (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
The lack of interest of nurses to used screening instruments for dysphagia at stroke centers and nerve spaces wasa strong reason for the development of the dysphagia screening website. This was to facilitate nurses in screeningpatients with dysphagia quickly. This study aimd to see the level of nurse satisfaction on the performance ofdysphagia screening websites. Quantitative research was used with total sampling techniques to 25 nurses. Itwas conducted on July to August 2019. Data collection used a nurse satisfaction level questionnaire after usingthe dysphagia screening website with results 8.0% were quite satisfied, 68.0% were satisfied and 24.0% werevery satisfied for the dysphagia screening website. As many as 88.0% chose dysphagia screening websites toscreen for stroke patients, 8.0% chose others that wanted this website to be developed into an offline applicationso that it could be used at any time and 4.0% chose to continue to screen for dysphagia by manual or check liston paper. Most respondent expressed the satisfaction in using dysphagia screening websites as seen from thelevel of satisfaction obtained.